Multicast communication protocol based on quantum key distribution against trojan horse attacking - Hong-yang MA; Xing-kui FAN (Tongxin xuebao)
A multicast communication protocol over quantum channel against Trojan horse attacking was proposed, in the network with one source quantum node and M target quantum nodes. The source quantum node is to build 2n+δ quantum EPR state, and to send sequence tags. In the sending sequence, n are selected randomly as the test states. Channel test is carried out with the inequality of CHSH. The rest n+δ of sending sequence transform into non-orthogonal state as the key. The key is block encoded as cipher text which is to be copied into M with optimal universal quantum cloning and sent to each target quantum node. After target quantum node receiving cipher text, decoding is conducted. The communication protocols of throughput, channel utilization, security proof were analyzed theoretically. By analyzing, the protocol can effectively counter Trojan horse attacking, guarantee the multicast communication information safely.